2021
DOI: 10.9734/ajess/2021/v16i130393
|View full text |Cite
|
Sign up to set email alerts
|

Deaf Educators’ Attitudes towards Inclusive Education in the Gauteng Province, South Africa

Abstract: This study aimed to explore the nature of the attitudes of Deaf educators towards inclusive education. The respondents were a non-probability sample of seven educators (Speaking educators = 3 and Deaf educator = 4) aged between 40 years and 55 years and with more than five years of teaching Deaf learners. A questionnaire with open-ended questions was designed and piloted before being administered. The data collected was analysed thematically. The results show that the respondents have a negative attitude towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…How an education system is structured (i.e., full inclusion, or mainstream and special education) also seem to have an impact on how positively or negatively the viability of inclusive education is viewed (Nel, 2018;Friesen and Cunning, 2020). In the contexts (especially South Africa) where there is an emphasis on human rights and social justice there is a general belief that inclusive education is the right thing to do, but practical challenges limit the successful implementation thereof (Mdikana et al, 2007;Savolainen et al, 2012;Ainscow, 2014;Nel, 2018;Adigun, 2021;Ismailos et al, 2022). Regarding the transformation of initial teacher education programes, international studies by Pantić and Florian (2015), Florian and Camedda (2020), Lehtomäki et al (2020) as well as Miškolci et al (2021) found that ITE programes generally have two main approaches.…”
Section: Background To This Study International Contextmentioning
confidence: 99%
“…How an education system is structured (i.e., full inclusion, or mainstream and special education) also seem to have an impact on how positively or negatively the viability of inclusive education is viewed (Nel, 2018;Friesen and Cunning, 2020). In the contexts (especially South Africa) where there is an emphasis on human rights and social justice there is a general belief that inclusive education is the right thing to do, but practical challenges limit the successful implementation thereof (Mdikana et al, 2007;Savolainen et al, 2012;Ainscow, 2014;Nel, 2018;Adigun, 2021;Ismailos et al, 2022). Regarding the transformation of initial teacher education programes, international studies by Pantić and Florian (2015), Florian and Camedda (2020), Lehtomäki et al (2020) as well as Miškolci et al (2021) found that ITE programes generally have two main approaches.…”
Section: Background To This Study International Contextmentioning
confidence: 99%
“…Such studies also include Mdikana et al (2007) who examined the attitudes of student teachers in Johannesburg towards the inclusive education of learners with special educational needs. Similarly, Kuyini and Desai's (2007) and Ocloo and Subbey's (2008) research in Ghana studied teachers' attitudes towards inclusive education.…”
Section: Bottlenecks To Inclusive Educationmentioning
confidence: 99%